Construction of the province Balochistan in Pakistani Media - Muhammad Tarique; Dr Lubna Shaheen (Journal of Peace, Development and Communication, 2022)
The biggest among all provinces of Pakistan, Balochistan comprises 44% of the entire landmass of the country. The geo-strategic vitality of the province manifests in its longest coastal belts, active longer borders with Afghanistan and China and Persia, and its location at the neck of Central Asia. Such and many other features make Balochistan, a treasure in the eyes of national and international actors. Abundant in natural resources, the province is considered the breadbasket of Pakistan. But unfortunately, the province has been facing chronic unrest and turmoil for decades. The succeeding federal governments have taken multiple steps to identify and resolve the causes of unrest in Balochistan through various socio-economic and political measures as well as deployments of law enforcement personnel. Not only does instability persist but conflict rises to new heights including the element of secession which continued till the present. The research paper explores dimensions of unrest through the coverage of national news media by employing Critical discourse analysis with the essence of peace journalism theory. It is found that the province of Balochistan as well as Balochs (the majority race of Balochistan) are marginalized by the media. This research particularly sheds light on the construction of the province of Balochistan, that how the place is marginalized in terms of ‘out of reach’, ‘dangerous place’, and more or so ‘stop developing Balochistan’ in the mainstream national press.